KONTRIBUSI LINGKUNGAN KELUARGA DAN LINGKUNGAN SEKOLAH BERBASIS AGAMA DENGAN PRESTASI BELAJAR SISWA SEKOLAH DASAR - Taofik Taofik; Muhammad Nur Wangid (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
The first education that humans get when they are children is informal education in the family environment. The existence of parents in informal education has a strong influence on each child. The family is the first and foremost educational institution. First and foremost because children are born and learn through the closest person, namely in the family institution. Education received by children is natural and informal due to the learning process in the form of socialization of values and skills in everyday life. and The second place of education for children after the family environment is the school environment. School is an institution officially organizing education. The main objective of establishing a school is to develop the potential of each child through teaching and learning activities in accordance with the applicable curriculum standards. This study aims to determine the relationship between family environment and faith based school environment and learning achievement. This research was quantitative correlational. The population was all students of fifth grade of faith based elementary school in Magelang as many as 392 students. The sample was 198 students, selected by purposive random proportional sampling technique. The study data were collected with family environment questionnaire, faith based school environment questionnaire, and documentation of learning achievement. Validity test was done by expert judgment and with the help of SPSS 20.0 for Windows. Reliability testing used Cronbach's alpha technique. The results showed that: (1) there was a positive relationship between the family environment and learning achievement, the value of a=0.000 and correlation of 0.678; (3) there was a positive relationship between faith based school environment and learning achievement, the value of a=0.000 and correlation of 0.542; (5) there was a positive relationship between family environment and faith based school environment with learning achievement, the value of a=0.000 and the correlation of 0.779.